Flawed eaudiobook - Wolff, Tracy (Ethan Frost, 2017)
I told myself I'd never trust Miles Girard, no matter how brilliant or sexy he may be. His sister, Chloe—Ethan Frost's wife—is my best friend, but I know just how low Miles will stoop to get what he wants. Now he's the last thing I want: my boss. Growing up, I had it all—except for the sense that I belonged. And when a mistake from my past surfaces in the press, my parents don't hesitate to cut me off. But surprisingly, Miles offers me a helping hand. Before I know it, our relationship turns unprofessional in the hottest ways. Of course, he still drives me crazy. But when I'm dealt the ultimate blow, Miles is there for me. And maybe he's the one I've been looking for all along. Contains mature themes.